Antibody responses to Sinopharm/BBIBP-CorV in pregnant mothers in Sri Lanka. - Chandima Jeewandara; K A Chintha S Jayampathi; Thushali Ranasinghe; Inoka Sepali Aberathna; Banuri Gunasekara; Saubhagya Danasekara; Thashmi Nimasha; Heshan Kuruppu; Osanda Dissanayake; Nayanathara Gamalath; Dinithi Ekanayake; Jewantha Jayamali; et al. (Public Library of Science (PLoS), 2022)
Background There are limited data regarding the safety and immunogenicity of the Sinopharm/BBIBP-CorV vaccine in pregnancy. Therefore, we sought to investigate the antibody responses and maternal and fetal adverse events following this vaccine in pregnant mothers in Sri Lanka. Methods and findings SARS-CoV-2 receptor binding domain (RBD) specific total antibodies and ACE2 blocking antibodies were measured by ELISA in pregnant mothers (n = 94) who received the vaccine in the first (n = 2), second (n = 57) and third (n = 33) trimester of pregnancy. Data regarding adverse events and fetal and maternal outcomes were obtained from the women once they delivered. No adverse maternal or fetal complications reported such as miscarriage, thrombotic events, hypertensive disorders, fetal death, preterm delivery, or congenital anomalies were reported. 58/94 (61.7%) had RBD binding antibodies and were found to be seropositive at the time of recruitment. All women seroconverted after the second dose and 31/36 previously uninfected women and 57/58 previously infected women gave a positive response to ACE2 blocking antibodies. The RBD binding antibody levels (p = 0.0002) and ACE2 blocking antibodies (p<0.0001) were significantly higher in previously infected individuals post-second dose compared to uninfected individuals. Conclusions The Sinopharm/ BBIBP-CorV vaccine appeared safe and induced high seroconversion rates and ACE2 blocking antibodies in pregnant mothers in the second and third trimester in pregnancy. However, the RBD binding antibodies and ACE2 blocking antibodies post-second dose were significantly higher in previously infected pregnant mothers post-second dose, suggesting that two doses of the vaccine are likely to be less immunogenic in previously unexposed individuals.